The best american short stories 2021 eaudiobook - Ward, Jesmyn (Best American Short Stories., 2021)
A collection of the year's best stories selected by celebrated two-time National Book Award winner Jesmyn Ward In her introduction to The Best American Short Stories 2021, guest editor JesmynWard says that the best fiction offers the reader a "sense of repair."The stories in this year's collection accomplish just that, immersing the reader in powerfully imagined worlds and allowing them to bring some of that power into their own lives. From a stirring portrait of Rodney King's final days to a surreal video game set in the Middle East,with real consequences, to an indigenous boy's gripping escape from his captors, this collection renders profoundly empathetic depictions of the variety of human experience. These stories are poignant reminders of the possibilities of fiction: as you sink into world after world, become character after character, as Ward writes,you"forget yourself, and then, upon surfacing, know yourself and others anew. The Best American Short Stories 2021 includes GABRIEL BUMP BRANDON HOBSON DAVID MEANS JANE PEK TRACEY ROSE PEYTON GEORGE SAUNDERS BRYAN WASHINGTON KEVIN WILSON C PAM ZHANG and others Performed by Lisa Flanagan, Robin Eller, Tre Hall, Katy Tang, Emily Ellet, Ryan Vincent Anderson, Alex Meraz-Mon, Adan Rocha, Piper Goodeve, Frankie Maria Corzo, Sterling Sulieman, JD Jackson, Brittany Pressley, Robert Fass, Bahni Turpin, Jonathan Davis, Priya Ayyar, Graham Halstead, Michael Crouch, and Catherine Ho